Different measures of blood pressure in primary health care in Saudi Arabia - Hassan, Khaled M.; Rahali, Hadil E.; Balamash, Hisham M.; Alanazi, Reem K.; Almatroudi, Naief S.; Alsairra, Munirah N.; Alhobera, Anfal H.; Alhobera, Abdullah H.; Alolah, Ahmed A.; Shok, Ali A.; Althumairy, Mohammed A.; Alghuraybi, Shaima M.; et al. (International Journal Of Community Medicine And Public Health, 2020)
Background: Objective of the study was to be able to know various measurement or devices for blood pressure (BP) used in primary care (PC). Methods: Cross-sectional multicenter study, sample is consecutive cases, study done in kingdom of Saudi Arabia in health institution of Primary care that treat patients who already diagnosed with hypertension aged more than 18 years old, the method used in the study is observation of devices which measure blood pressure through two following BP measurements. Results: Blood pressure was measured for 14,137 from 3,592 PC physicians, blood pressured measured by a mercury sphygmomanometer, in 69.8% of the patients, while it is measured by electronic device in 16.5% but measured by aneroid manometer in 11.8% while 1.9% measured by more of a measurement method. Electronic devices and aneroid manometers were the most used measurement of blood pressure in rural areas. Also, there were differences in the BP values between different methods of the measurement. Conclusions: The best methods of blood pressure measurement between medical staff is mercury sphygmomanometers and aneroid devices in primary care and to avoid biases in the measurement we encourage to use electronic devices to measure BP.